O acalanto na creche: a escuta que enlaça e ecoa na fala da criança. - Silva, Elisangela Maria da (2019)
Entry into the language field. Psychoanalysis. Acalanthus. Voice. In your resonances. Catch. Listening. Subscription. Lalingua. Points that intertwine throughout this study seeking to give a path to impasses that arise from two fields, the acalanthus and the child’s speech, considered here like an enigma. These impasses have converged in a "construction" that can be thought as a musical work, in that melodies overlap, harmonies are created and ideas are born disappearing and reappearing in an enigmatic "construction" that have sustained the choice of the theme of this research: the acalanthus as element that affects the crossing of the child from infans to speaker. This sense, the present study sought to investigate the place occupied by acalanthus in the child's entry into the language field. To this end, we’ve based on the theoretical Linguistic Interactionism by Lemos, C. T., based on European structural linguistics and Freud lacanian psychoanalysis. This study also sought to investigate how the constitutive elements of acalanthus return in the child's body, to analyze the position in the child is placed during the acalanthus and to analyze the effects of acalanthus on the child's relationship with the adult / teacher / assistant. To address these objectives, the research was conducted in a public daycare located in Ipojuca/PE. Regarding the methodological aspects of the research, we’ve opted for a qualitative approach of the case study, in which we’ve counted on two adults, a teacher and an assistant, and four children, between one and three years old, registered in Childish I. For data collection were performed videophonographic records containing the aspects of interactions between the children / teacher / auxiliary, these records were analyzed and interpreted through a methodological proposal based on the theoretical framework of Linguistic Interactionism by Lemos, C.T., and also based on psychoanalytic theory. The results have indicated that the acalanthus when it thought from the desiring addressing to the other, can make the scene create, allowing the repetition of the initial experiences and, at the same time, always tangent to the new. In other words, the acalanthus allows from the entwine with the desire of the Other that the child becomes entangled and constitutes another way of positioning in the language.